HANDLING OF REFUGEES AND ASYLUM SEEKERS AT IMMIGRATION DETENTION HOUSES IN INDONESIA BASED ON INTERNATIONAL REFUGE LAW PROVISIONS - Muhammad Azzam Alfarizi; Asto Yudho Kartiko; Dwi Nuryani (Polteknik Imigrasi, 2022)
Refugees and asylum seekers are often the topic of problems between the receiving State and the United Nations High Commissioner for Refugees (UNHCR) as a mandate from the United Nations (UN) to protect refugees and help refugees find solutions to their situation. In order to minimize the impact of the existence of foreigners as illegal immigrants who later declare themselves as asylum seekers and refugees, it is necessary to have arrangements that provide equality and uniformity of direction in immigration handling and treatment. The implementing provisions of these regulations are derived from the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number M.05.IL.02.01 of 2006 concerning Rudenim which regulates temporary shelters for foreigners who violate applicable laws and regulations, especially in the field of immigration. For example, the protection status of Rohingya refugees in Indonesia. This research uses a statutory approach, a conceptual approach, and a case approach.